La terapia visual como refuerzo de las insuficiencias de convergencia en niños de 7-10 años, Unidad Educativa José María Estrada Coello, Babahoyo – Los Ríos, octubre 2018 – abril 2019 - Carriel Mosquera, Victoria Gabriela (2019)
The present study analyzed the visual therapy as a reinforcement of the convergence insufficiency, to achieve the objective the study was made to third and fourth year students of the Educational Unit "José María Estrada Coello" The insufficiency of convergence is the inability to converge both eyes in the same point, it generates difficulties in the students at the time of carrying out school activities for it to detect and treat it on time is important, it was worked with 98 students of which it was evidenced that they presented failure of convergence 26%, the investigation it was qualitative and quantitative, the descriptive, diagnostic and explanatory method was used to demonstrate the relationship of the population with the study variables, whether the hypothesis was related to the study group of children aged 7 to 10 years later, it was concluded that it is important to perform regular optometric tests students of third and fourth year, especially if they have low school performance, so the insufficiency of convergence was related to poor school performance in terms of reading and writing, so at the end a guide is applied as an alternative proposal for teachers , optometrists and parents work together and decrease the symptoms of convergence insufficiency.